NLRP3‐mediated dysfunction of mitochondria leads to cell death in CFT073‐stimulated macrophages. (18th October 2021) - Verma, Vivek; Kumar, Parveen; Gupta, Surbhi; Yadav, Sonal; Dhanda, Rakesh Singh; Yadav, Manisha
Abstract: Urinary tract infections (UTIs) are commonly caused by uropathogenic E coli (UPEC), which uses different mechanisms to invade and damage hosts. NLRP3 inflammasome activation is a double‐edged sword, although beneficial in the clearance of dysfunctional cells or pathogens but results in severe pathologies, if unchecked. NLRP3 inflammasome plays a critical role in UPEC‐mediated inflammatory cell death during UPEC infection, though the effects of its activation are not clearly understood yet. Inflammatory response usually involves Signal‐I (MyD88, TRIF and NF‐κB signalling) and Signal‐II (Inflammasome oligomerization) which is induced by the pathogen‐associated molecular patterns during infection. We observed that proIL‐1β and mature IL‐1β remained unchanged on inhibition of MyD88 and TRIF‐dependent signalling in CFT073‐insulted THP‐1m. However, inhibition of NF‐κB pathway resulted in concomitant reduction in both pro‐ and cleaved forms of IL‐1β in cellular extracts but there was no change in IL‐1 β secretion. Interestingly, inhibition of NLRP3 completely abolished the maturation and release of cleaved form of IL‐1β. Additionally, NLRP3‐mediated mitochondrial dysfunction (increased mito‐ROS and mitochondrial hyperpolarization) resulting in cell death was induced in CFT073‐insulted THP‐1m, which was rescued upon inhibition of NLRP3 activation. Therefore, we have concluded that UPEC uses a different signal‐I pathway (other than MyD88 and TRIF), while NLRP3 inflammasome is the major signal‐II for the induction of inflammatory response. Further, this study signifies the importance of NLRP3‐mediated mitochondrial dysfunction in CFT073‐induced inflammatory cell death of macrophages, which could be rescued through inhibition of NLRP3 activation.